Foot traffic on turf primarily shaped the endophytic bacteriome of the soil-rhizosphere-root continuum - Akther, Sayada Momotaz; Hu, Jialin; Miller, Grady; Shi, Wei (Frontiers in Microbiology, 2025)
Foot traffic on turf can cause grass wear-stress and soil compaction, adversely impacting turf health. The root microbiome, consisting of diverse microbes, plays a crucial role in enhancing plant resilience to abiotic stressors. However, the effects of foot traffic on these microbes and the mechanisms they employ to help plant survival remain largely unknown. Here, we investigated how foot traffic affected microbial communities of the root endosphere, rhizosphere, and bulk soil in Bermudagrass (Cynodon spp.) and Zoysiagrass (Zoysia spp.) turfs. Foot traffic was simulated to mimic six professional football games per week using a modified Baldree traffic simulator. High-throughput amplicon sequencing targeting 16S rRNA for bacteria and ITS for fungi was employed to analyze microbial communities. Foot traffic slightly and significantly reduced soil moisture and inorganic nitrogen, likely due to soil compaction and associated impairment on microbial activity. Microbial alpha diversity varied across microhabitats, with no discernible effect of foot traffic. However, microbial community composition was impacted by foot traffic, being more pronounced on bacteria of the root endosphere and on fungi of the bulk soil. In light of the genetic potential predicted by PICRUSt2, foot traffic enriched a few pathways of the endophytic bacteriome, including nitrifier denitrification (PWY7084) and mannosylglycerate biosynthesis (PWY5656). This indicated that root endophytes could help turfgrass to tolerate foot traffic via controls on the concentration of nitric oxide, the signaling molecule for root growth, and mannosylglycerate, the compatible solute for protecting enzymes against osmotic stress. Foot traffic also enhanced degradation pathways of carbohydrates and 4-coumarate, the constituent of turfgrass cell walls (PWY-3801, PWY-2221, PWY-7046), indicating the faster turnover of root tissues. Along the root-rhizosphere-bulk soil continuum, the bacteriome varied substantially in composition and also exhibited contrasting genetic potentials from stress alleviation to nutrient supply in coping with grass growth. But foot traffic had little effect on the genetic potential of bacteriome in rhizosphere and bulk soil. Our findings indicated that the endophytic bacteriome was more sensitive to foot traffic than the bacteriome in the rhizosphere and bulk soil and could potentially help turf survival via influences on plant signal molecules and compatible solutes.